Defining sustainable limits during and after intensification in a maritime agricultural ecosystem - Geoffrey R Squire (Ecosystem Health and Sustainability, 2017)
Introduction: Intensification of agricultural ecosystems in the 20th century proceeded by a series of innovations that initially ensured food security, but had negative consequences for the in-field and wider environments. A case study in the north Atlantic zone maritime cropland of the UK identified three phases: (1) reorganization between 1940 and 1960, (2) intensification leading to tripling of grain output (1960–1990), and (3) a leveling of output (1990–2015). Outcomes: Innovations that caused the changes together with their effect on life forms, ecological processes and the evolving social, economic and biophysical conditions are identified. Attempts to design future sustainable systems are hampered by the absence of a baseline before intensification, by inadequate knowledge of in-field processes, and by uncertainty over “safe ranges” in which processes can operate without causing long-term system decline. Safe ranges are examined for three attributes recorded over all three phases, namely grain output, fertilizer input and the wild seedbank flora. The lower limits for grain and nitrogen were quantified as those that ensure grain security. Tentative upper limits were identified as those that were economically acceptable to farming in the face of major external perturbations related to food policy and environmental protection. Within these upper limits, fields can maintain a generalist wild species seedbank that supports a farmland food web. Conclusion: Some properties of the ecosystem therefore attained stability in phase 3. However, evidence of degrading soil, increasing pesticide use to maintain yield and collapse of specialist plant functions such as nitrogen fixation and pollination, suggest the system is moving toward a phase of decline.